2003
DOI: 10.1177/0013916502250133
|View full text |Cite
|
Sign up to set email alerts
|

The Role Of Permanent Student Artwork In Students’ Sense Of Ownership In An Elementary School

Abstract: The objective of this study is to determine if the physical design of learning environments can foster a sense of student ownership in the learning process. Accommodation of permanent student artwork to school interior spaces may enhance student ownership. Sense of ownership incorporates personalization, sense of control, territoriality, and involvement. The authors uncover a significant association between school design and students’ sense of ownership. Furthermore, within a school incorporating permanent art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Schools that include permanent student artwork in the interior spaces of school buildings also will foster student ownership (Killeen, Evans, & Danko, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Schools that include permanent student artwork in the interior spaces of school buildings also will foster student ownership (Killeen, Evans, & Danko, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Killeen, Evans and Danko [64] studied the impact of physical learning environments on students' sense of ownership in learning. Overall the investigators found that fourth and fifth grades students in the experimental school that provided permanent displays of student work reported a significantly higher sense of ownership in the learning environment than students in a school where only temporary displays were allowed.…”
Section: Aesthetic Literature Reviewmentioning
confidence: 99%
“…In welldesigned school environments students often feel more valued (Catling, 2005) and feel more attached to their schools (Killeen, Evans, & Danko, 2003;Kumar et al, 2008), which Spencer and Woolley (2000) claim is important in the formation of children's personal identity. The design of school grounds has been shown to impact students' level of physical activity (Collins & Coleman, 2008;Ozdemir & Yilmaz, 2008), and inadequate design of non-classroom spaces may have adverse effects on students either by way of problem behaviors (Kumar et al, 2008) or negative emotions (Thurber & Malinowski, 1999).…”
Section: School Environment and Childrenmentioning
confidence: 99%